Economic complexity and the green economy - Mealy, P; Teytelboym, A (Elsevier, 2020)
Which countries are likely to have the productive capabilities to thrive in the green economy? How might countries reorient their existing industrial structures to be more competitive in an environmentally friendly world? To investigate these questions, this paper develops a novel methodology for measuring productive capabilities to the green economy. By constructing a new comprehensive dataset of traded green products and drawing on economic complexity methods, we rank countries in terms of their ability to export complex green products competitively. We show that higher ranked countries are more likely to have higher environmental patenting rates, lower CO2 emissions, and more stringent environmental policies even after controlling for per capita GDP. We then examine countries' potential to transition into green products in the future and find strong path dependence in the accumulation of green capabilities. Our results shed new light on green industrialisation and have a number of implications for green industrial policy.